ANTIDIABETIC ACTIVITY OF LEAF EXTRACT OF Clerodenrum fragrans Vent Willd IN Rattus novergicus INDUCED BY ALLOXAN - Silaban, Saronom (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2022)
Sarang banua plants are grown in Simalungun, North Sumatra, Indonesia, and have been used by the community as traditional medicinal plants. Sarang banua plant is a type of Clerodendrum fragrans Vent Willd, including the family Verbenaceae. This study aimed to determine the antidiabetic activity of the leaf extract of sarang banua (C. fragrans Vent Willd) in white male rats (Rattus novergicus) induced by alloxan. This study used a RAL design with seven treatments, namely (K0) standard feed, (K1) Na-CMC 0.5%), (K2) metformin, (K3) ethanol extract 100 mg/kg bw, 200 mg/kg bw (K4), 300 mg/kg bw (5), (K6) ethyl acetate extract 200 mg/kg bw and 300 mg/kg bw (K7). Groups K1 to K7 were induced by alloxan before being given treatment. Each treatment was replicated three times. The results showed that the application of leaf extract of the C. fragrans affected on reducing the blood glucose levels of alloxan-induced rats. The used of ethanolic extract of C. fragrans 100 mg/kg bw resulted in the highest percentage decrease in blood glucose (54.46 ± 5.60%) of hyperglycemic rats induced by alloxan, close to a positive control (56.63 ± 1.86%).